2016
DOI: 10.1111/jam.13211
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among hygiene indicators in take-away foodservice establishments and the impact of climatic conditions

Abstract: This study provides another perspective into the possible nature of cross-contamination and foodborne outbreaks originating in foodservice establishments and brings to attention the necessity of analysing various climatic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Extreme weather events such as floods and droughts may lead to contamination of soil, agricultural lands, water and food and animal feed with pathogens, chemicals and other hazardous substances, originating from sewage, agriculture and industrial settings (Tirado et al, 2010). Djekic et al (2016b) In general, main stream environmental research in food industry can be categorized as product, process or system oriented. Product based perspective focuses on a specific food and its environmental impact throughout the food chain/life cycle.…”
Section: Climate Change and Food Safetymentioning
confidence: 99%
“…Extreme weather events such as floods and droughts may lead to contamination of soil, agricultural lands, water and food and animal feed with pathogens, chemicals and other hazardous substances, originating from sewage, agriculture and industrial settings (Tirado et al, 2010). Djekic et al (2016b) In general, main stream environmental research in food industry can be categorized as product, process or system oriented. Product based perspective focuses on a specific food and its environmental impact throughout the food chain/life cycle.…”
Section: Climate Change and Food Safetymentioning
confidence: 99%
“…On the other hand, higher precipitation might allow development of environmentally mediated bacteria transmission pathways (Lal, Hales, French, & Baker, 2012) and consequently greater TPC. Relationship between various hygienic indicators and climatic conditions, mostly temperature and precipitation, have been confirmed in various studies (Djekic et al, 2016). It has been shown that climatic conditions have an impact on food safety as well as on the prevalence of foodborne diseases under certain circumstances (Bezirtzoglou, Dekas, & Charvalos, 2011;Jacxsens et al, 2010).…”
Section: Introductionmentioning
confidence: 80%
“…and the Firmicute/Proteobacteria ratio were observed by the warmer or colder seasons (Supplementary Figure 2). Similarly, Djekic et al (2016) reported that the climate condition in foodservice establishments affects the presence of hygiene indicators, such as Enterobacteriaceae and Staphylococcus.…”
Section: Discussionmentioning
confidence: 98%